Prognostic value of global longitudinal strain in patients with preserved left ventricular systolic function: A cardiac magnetic resonance real-world study - Preeyaporn Janwetchasil; Ahthit Yindeengam; Rungroj Krittayaphong (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Myocardial strain is a more sensitive parameter for cardiac function evaluation than left ventricular ejection fraction (LVEF). This study aimed to assess the predictive value of left ventricular global longitudinal strain (LV-GLS) by feature tracking-cardiac magnetic resonance (FT-CMR) imaging in patients with known or suspected coronary artery disease (CAD) with preserved left ventricular systolic function. Methods: This retrospective cohort analysis enrolled patients with known or suspected CAD who underwent cardiac magnetic resonance imaging from September 2017 to December 2019. LV-GLS was analyzed via feature-tracking analysis. Patients with LVEF <50% were excluded. The composite outcome comprised all-cause death, non-fatal myocardial infarction, and heart failure. Results: There was a total of 2613 patients. Mean follow-up duration was 39.7 ± 13.9 months. During follow-up, 194 patients (7.4%) experienced a composite outcome. The best cutoff of LV-GLS in the prediction of composite outcome from receiver operating characteristics was −14.4%. Patients were classified into 2 groups according to the LV-GLS; 1489 (57.0%) had LV-GLS <−14.4% and 1124 (43.0%) had LV-GLS ≥−14.4%. Patients with LV-GLS ≥−14.4% had a significantly higher rate of composite outcome than LV-GLS <−14.4% patients (3.59 vs. 1.39 per 100 person-years, respectively; p < 0.001). Multivariable analysis showed that patients with LV-GLS ≥−14.4% had a significantly higher risk of experiencing a composite outcome event compared to global longitudinal strain <−14.4% patients (adjusted hazard ratio: 1.83, 95% confidence interval: 1.28-2.61; p = 0.001). Conclusion: LV-GLS by FT-CMR was shown to be useful for predicting the prognosis of patients with known or suspected CAD with preserved left ventricular systolic function. LV-GLS −14.4% was the identified cutoff for prognostic determination.